AI for retail : a practical guide to modernize your retail business through automation - Chaubard, Francois (John Wiley & Sons, Incorporated, 2023)
The coming of the AI revolution in brick-and-mortar retail In AI for Retail: A Practical Guide to Modernize Your Retail Business with AI and Automation, Francois Chaubard, AI researcher and retail technology CEO, delivers a practical guide for integrating AI into your brick-and-mortar retail business. In the book, you'll learn how to make your business more efficient by automating inventory management, supply chain, front-end, merchandising, pricing, loss prevention, e-commerce processes, and more. The author takes you step by step from no AI Strategy at all to implementing a robust AI playbook that will permeate through your entire organization. In this book, you will learn: How AI works, including key terminology and fundamental AI applications in retail How AI can be applied to the major functions of retail with detailed P&L analysis of each application How to implement an AI strategy across your entire business to double or even triple Free Cash Flow AI for Retail is the comprehensive, hands-on blueprint for AI adoption that retail managers, executives, founders, entrepreneurs, board members, and other business leaders have been waiting for.